The Underrepresentation of Older Adults in Clinical Trials: Toward Solutions for a Persistent Issue (BioLaw Journal - Rivista di BioDiritto, 2026)
The persistent underrepresentation of older adults in clinical trials constitutes a structural paradox in contemporary pharmaceutical research: those who are the primary recipients of medicinal products are often excluded from the evidentiary processes underlying their authorization. While widely documented in biomedical literature, its legal implications remain comparatively underexplored. This paper examines the issue from a legal and regulatory perspective, situating age-based exclusion at the intersection of scientific methodology, regulatory design, and fundamental rights protection. It reviews the main causes and consequences of underrepresentation and assesses current regulatory responses, including international soft law, U.S. policies, and the EU framework under Regulation (EU) No 536/2014, highlighting persistent gaps between formal commitments to representativeness and their practical implementation.
Keywords: clinical trials; inclusiveness in research; older adults; decentralized clinical trials; Ethics Committees